Functionalized ionic liquids based on vegetable oils for rare earth elements recovery. Issue 45 (16th July 2020) - Li, Fujian; Zeng, Jingyao; Sun, Xiaoqi
Abstract : Vegetable oil based ionic liquids for rare earth recovery. Abstract : Functionalized ionic liquids (FILs) based on vegetable oils have been directly synthesized and used for the first time to extract rare earth elements (REEs). Carbon dioxide gas is introduced to successfully strip REE-loaded FILs in the presence of water. The novel extraction process reveals some advantages of accessibility, biocompatibility and sustainability as well as cost efficiency.